Pengaruh Kepastian Hukum Lahan dan Tata Kelola Aset Terhadap Potensi Peningkatan Penerimaan Negara Bukan Pajak (PNBP) Melalui Realisasi Investasi - Elya Rifqiati (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to determine the effect of land legal certainty and asset management on the potential increase of PNBP mediated by investment realization. The primary data were obtained through questionnaires distributed to respondents who were relevant to the research context. The study population consisted of respondents who had knowledge of land management, asset governance, investment realization, and PNBP in the transmigration sector. The data were analyzed using PLS-based SEM. The results showed that land legal certainty and asset management had a significant effect on investment realization, this study also concluded that land legal certainty and investment realization had a significant effect on the potential increase in PNBP. Asset management has no direct effect on the potential increase in PNBP. Investment realization is able to mediate the relationship of the effect of land legal certainty and asset management on the potential increase in PNBP.